Prevalence of renal dysfunction and its influence on functional capacity in elderly patients with stable chronic heart failure - Stanojević Dragana; Apostolović Svetlana; Janković-Tomašević Ružica; Šalinger-Martinović Sonja; Pavlović Milan; Živković Milan; Božinović Nenad; Kutlešić-Kurtović Dušanka (Vojnosanitetski Pregled)
Bacground/Aim. Chronic heart failure (CHF) is highly prevalent and constitutes an important public health problem around the world. In spite of a large number of pharmacological agents that successfully decrease mortality in CHF, the effects on exercise tolerance and quality of life are modest. Renal dysfunction is extremely common in patients with CHF and it is strongly related not only to increased mortality and morbidity but to a significant decrease in exercise tolerance, as well. The aim of our study was to investigate the prevalence and influence of the renal dysfunction on functional capacity in the elderly CHF patients. Methods. We included 127 patients aged over 65 years in a stable phase of CHF. The diagnosis of heart failure was based on the latest diagnostic principles of the European Society of Cardiology. The estimated glomerular filtration rate (eGRF) was determined by the abbreviated Modification of Diet in Renal Disease (MDRD2) formula, and patients were categorized using the Kidney Disease Outcomes Quality Initiative (K/DOQI) classification system. Functional capacity was determined by the 6 minute walking test (6MWT). Results. Among 127 patients, 90 were men. The average age was 72.5 ± 4.99 years and left ventricular ejection fraction (LVEF) was 40.22 ± 9.89%. The average duration of CHF was 3.79 ± 4.84 years. Ninty three (73.2%) patients were in New York Heart Association (NYHA) class II and 34 (26.8%) in NYHA class III. Normal renal function (eGFR ≥ 90 mL/min) had 8.9% of participants, 57.8% had eGFR between 60-89 mL/min (stage 2 or mild reduction in GFR according to K/DOQI classification), 32.2% had eGFR between 30-59 mL/min (stage 3 or moderate reduction in GFR) and 1.1% had eGFR between 15-29 mL/min (stage 4 or severe reduction in GFR). We found statistically significant correlation between eGFR and 6 minute walking distance (6MWD) (r = 0.390, p < 0.001), LVEF (r = 0.268, p < 0.05), NYHA class (ς = -0.269, p < 0.05) and age (r = - 0.214, p < 0.05). In multiple regression analysis only patients’ age was a predictor of decreased 6MWD < 300 m (OR = 0.8736, CI = 0.7804 - 0.9781, p < 0.05). Conclusion. Renal dysfunction is highly prevalent in the elderly CHF patients. It is associated with decreased functional capacity and therefore with poor prognosis. This study corroborates the use of eGFR not only as a powerful predictor of mortality in CHF, but also as an indicator of the functional capacity of cardiopulmonary system. However, clinicians underestimate a serial measurement of eGFR while it should be the part of a routine evaluation performed in every patient with CHF, particularly in the elderly population.